Diabetes and calcific aortic valve disease: implications of glucose-lowering medication as potential therapy - Liu, Feng; Cai, Haipeng (Frontiers in Pharmacology, 2025)
Calcific aortic valve disease (CAVD) is a progressive disease, of which the 2-year mortality is >50% for symptomatic disease. However, there are currently no pharmacotherapies to prevent the progression of CAVD unless transcatheter or surgical aortic valve replacement is performed. The prevalence of diabetes among CAVD has increased rapidly in recent decades, especially among those undergoing aortic valve replacement. Diabetes and its comorbidities, such as hypertension, hyperlipidemia, chronic kidney disease and ageing, participated jointly in the initiation and progression of CAVD, which increased the management complexity in patients with CAVD. Except from hyperglycemia, the molecular links between diabetes and CAVD included inflammation, oxidative stress and endothelial dysfunction. Traditional cardiovascular drugs like lipid-lowering agents and renin-angiotensin system blocking drugs have proven to be unsuccessful in retarding the progression of CAVD in clinical trials. In recent years, almost all kinds of glucose-lowering medications have been specifically assessed for decelerating the development of CAVD. Based on the efficacy for atherosclerotic cardiovascular disease and CAVD, this review summarized current knowledge about glucose-lowering medications as promising treatment options with the potential to retard CAVD.